Assessing the Impact of Defects on Lead‐Free Perovskite‐Inspired Photovoltaics via Photoinduced Current Transient Spectroscopy - Pecunia, Vincenzo; Zhao, Jing; Kim, Chaewon; Tuttle, Blair R.; Mei, Jianjun; Li, Fengzhu; Peng, Yueheng; Huq, Tahmida N.; Hoye, Robert L. Z.; Kelly, Nicola D.; Dutton, Siân E.; Xia, Kai; et al. (Advanced energy materials, 2021)
The formidable rise of lead‐halide perovskite photovoltaics has energized the search for lead‐free perovskite‐inspired materials (PIMs) with related optoelectronic properties but free from toxicity limitations. The photovoltaic performance of PIMs closely depends on their defect tolerance. However, a comprehensive experimental characterization of their defect‐level parameters—concentration, energy depth, and capture cross‐section—has not been pursued to date, hindering the rational development of defect‐tolerant PIMs. While mainstream, capacitance‐based techniques for defect‐level characterization have sparked controversy in lead‐halide perovskite research, their use on PIMs is also problematic due to their typical near‐intrinsic character. This study demonstrates on four representative PIMs (Cs3Sb2I9, Rb3Sb2I9, BiOI, and AgBiI4) for which Photoinduced Current Transient Spectroscopy (PICTS) offers a facile, widely applicable route to the defect‐level characterization of PIMs embedded within solar cells. Going beyond the ambiguities of the current discussion of defect tolerance, a methodology is also presented to quantitatively assess the defect tolerance of PIMs in photovoltaics based on their experimental defect‐level parameters. Finally, PICTS applied to PIM photovoltaics is revealed to be ultimately sensitive to defect‐level concentrations <1 ppb. Therefore, this study provides a versatile platform for the defect‐level characterization of PIMs and related absorbers, which can catalyze the development of green, high‐performance photovoltaics. Photoinduced Current Transient Spectroscopy (PICTS) is a versatile, high‐sensitivity technique for the defect‐level characterization of lead‐free perovskite‐inspired materials (PIMs). Applied to four representative PIMs (Cs3Sb2I9, Rb3Sb2I9, BiOI, and AgBiI4), PICTS quantifies their defect‐level parameters and delivers quantitative insight into their defect tolerance through the One‐Center Defect‐Tolerance Analysis. PICTS can catalyze the development of defect‐tolerant perovskites/perovskite‐inspired absorbers for high‐performance photovoltaics.